A system for beach video-monitoring: Beachkeeper plus - Brignone, Massimo (2012)
A suitable knowledge of coastal systems, of their morphodynamic characteristics and their response to storm events and man-made structures is essential for littoral conservation and management. Nowadays webcams represent a useful device to obtain information from beaches. Video-monitoring techniques are generally site specific and softwares working with any image acquisition system are rare. Therefore, this work aims at submitting theory and applications of an experimental video monitoring software: Beachkeeper plus, a freeware non-profit software, can be employed and redistributed without modifications. A license file is provided inside software package and in the user guide. Beachkeeper plus is based on Matlab ® and it can be used for the analysis of images and photos coming from any kind of acquisition system (webcams, digital cameras or images downloaded from internet), without any a-priori information or laboratory study of the acquisition system itself. Therefore, it could become a useful tool for beach planning. Through a simple guided interface, images can be analyzed by performing georeferentiation, rectification, averaging and variance. This software was initially operated in Pietra Ligure (Italy), using images from a tourist webcam, and in Mar del Plata (Argentina) using images from a digital camera. In both cases the reliability in different geomorphologic and morphodynamic conditions was confirmed by the good quality of obtained images after georeferentiation, rectification and averaging. © 2012 Elsevier Ltd.